2008
DOI: 10.1128/iai.00553-08
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial and Mesenchymal Cells in the Bovine Colonic Mucosa Differ in Their Responsiveness toEscherichia coliShiga Toxin 1

Abstract: Some Shiga toxin-producing Escherichia coli (STEC) strains, enterohemorrhagic E. coli strains, are food-borne pathogens which evoke life-threatening diseases in humans (26). Cattle and other ruminants can shed STEC for long periods and are a major reservoir for zoonotic STEC (6,61,70,72). Emerging human STEC infections make the reduction of STEC shedding by reservoir species a current challenge in veterinary public health.Several lines of evidence indicate that STEC adherence to bovine intestinal epithelial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 73 publications
(80 reference statements)
0
31
0
Order By: Relevance
“…Mucosal antibodies against membrane-associated and secreted STEC proteins, predominantly those implicated in bacterial adhesion to the bovine intestinal mucosa, are readily induced upon experimental STEC infection of calves (40) and may contribute to the reduction in STEC shedding by vaccinated animals (48). Most STEC strains possess adherence traits, but the Stx secreted do not immediately act on bovine epithelial cells (56). Bovine Stx target cells of the adaptive immune system are situated beyond the epithelial (34,37,57).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mucosal antibodies against membrane-associated and secreted STEC proteins, predominantly those implicated in bacterial adhesion to the bovine intestinal mucosa, are readily induced upon experimental STEC infection of calves (40) and may contribute to the reduction in STEC shedding by vaccinated animals (48). Most STEC strains possess adherence traits, but the Stx secreted do not immediately act on bovine epithelial cells (56). Bovine Stx target cells of the adaptive immune system are situated beyond the epithelial (34,37,57).…”
Section: Discussionmentioning
confidence: 99%
“…Strains representative of different PFGE patterns were selected, and the eae subtype was determined by PCR-restriction fragment length polymorphism analysis (51). Adhesion characteristics of the strains to HEp2-cells (ATCC CCL23; LGC-Promochem) and primary bovine colonic crypt cells (56) were detected by a modified Giemsa test (14). The ability to induce reorganization of intracellular actin filaments next to the point of bacterial adhesion was determined in the fluorescent-actin staining test (29), comprising an incubation step (3 h at 37°C) of cell monolayers with washed bacterial suspensions from an overnight culture, an intermediate washing step (cell culture medium) to remove unbound bacteria, and another incubation step (3 h at 37°C) to facilitate formation of a specific adherence pattern.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoey and colleagues 75 reported the finding of Stx receptors in crypt epithelial cells in the intestine, but the toxin does not traffic to the endoplasmic reticulum; it ends up in lysosomes, which probably prevents toxicity. Stamm and colleagues 76 identified novel mesenchymal, nonepithelial Stx target cells in the crypt area of the bovine colonic mucosa. These investigators reported that bovine crypt epithelial cells are resistant to the effects of Stx1, but some intestinal mucosal mesenchymal cells, preliminarily characterized as mucosal macrophages, are Stx1-responsive and may participate in the interaction of STEC with the bovine intestinal mucosa.…”
Section: Proposed Role Of Shiga Toxin In the Bovine Hostmentioning
confidence: 99%
“…Primary bovine colonic epithelial cells (BCEC prim ) were isolated according to the method of Föllmann et al (2000) with some modifications (Bridger et al 2010;Stamm et al 2008). Briefly, large intestine (colon ascendens) samples were isolated from freshly slaughtered cattle (18-24 months old) from the local abattoir.…”
Section: Isolation and Cultivation Of Bovine Colonic Epithelial Cellsmentioning
confidence: 99%